Donor site healing response to low-level laser therapy following skin graft surgery - Mahmoud Salah Salem; Haidy Nady Ashem; Salah Mohamed Abdelghani; Noha Mohamed Kamel (Physiotherapy Quarterly)
Introduction Skin grafting is an essential reconstructive technique for the healing of deep and extensive burns. Donor site problems are common complications after skin graft surgery. Speeding up the healing process at the donor site using low-level laser therapy helps avoid these problems. Objectives: The purpose of this research was to examine the efficacy of low-level laser therapy in promoting donor site healing in burn patients who underwent skin graft surgery.